Latent Class Analysis of Student Preferences for Teaching Styles in Mathematics Education at a College of Education in the Volta Region, Ghana - Kumah, Maxwell Seyram Kwame; Muktar, Babagana; Ayanwoye, Olubunmi Kayode; Adesina, Olugbenga Alani (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2024)
The purpose of the study was to investigate the preference of teaching styles of student teachers in learning mathematics This study employed a quantitative research approach using a descriptive survey design to explore the impact of teaching styles on mathematics learning among level 400 student teachers in three Colleges of Education in the Volta region of Ghana. The participants were purposively sampled to identify their preferred learning styles in mathematics. Out of 1489 students, 1338 (89.86%) successfully submitted their questionnaires, making them the final sample for analysis. The instrument, Student Preference for Learning Mathematics Questionnaire (SPLMQ), consisted of 10 items measured on a three-point Likert scale (Disagree, Don't Know, Agree) was used. Data analysis included fit indicators, Latent Class Analysis (LCA) plots, descriptive statistics, and inferential statistics, including a one-way ANOVA (Welch’s) and Games-Howell Post-Hoc Test. The findings indicated that student responses varied significantly across different teaching styles—Demonstrate, Facilitate, and Delegate. The ANOVA results showed significant differences in students' programs of study across the teaching preference classes (F = 10, p < 0.001). The post-hoc analysis revealed a significant difference between the Demonstrate and Delegate groups (t = -4.45, p < 0.001), suggesting distinct preferences in how these students approach mathematics learning based on the teaching strategies employed. These results suggest the importance of tailoring teaching styles to students' learning preferences to enhance mathematics outcomes.